A people and a nation - Ver Steeg, Clarence L. (Clarence Lester), 1922-2007.; Hofstadter, Richard, 1916-1970 (New York : Harper & Row, 1971)
A textbook tracing the history of the United States from the arrival of the first explorers to the present day.
Includes bibliographies and index.
900-999
Keywords: United States -- History; United States -- History; History